Sex Stereotyping towards Black Gay Man in Moonlight Movie: A Queer Study - Nabila Putri Ramdhany; Ali Mustofa (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This study seeks to find sex stereotypical act towards black gay men from Berry Jenkins' Moonlight (2016) using the Queer perspective. Sex stereotyping is an act when someone has a preconceived conception of how someone should be, act, or behave based on that person’s sex. Moonlight discusses Chiron's struggles with sexuality and personality, including his increasing physical and emotional violence. By adapting queer theory perform by Judith Butler's book Bodies That Matter: In the Discursive Limit of “Sex” it answered the aim of the study. In their book, Butler explains and breaks down the performativity of sex and body and how culture shapes them. In doing this study, both textual and film visual analysis will be applied to the following discussion: 1) determine forms of sex stereotyping in Moonlight; 2) reveal sex stereotyping towards black gay men exist in society in Moonlight. Throughout the analysis, sex stereotyping that happened toward Chiron struggling to cope with his culture as a black gay man formed Chiron’s alienation, heteronormativity, and homophobia. This act of stereotypical sex based on their skin color represent a backlash against their people.